Influence of Quality Improvement Activities and Direct Selling Through Mediated Partnership Model on Supply Chain, Farm-Gate Price and Indonesian Households Specialty Coffee Farmers’ Income - Diany Faila Sophia Hartatri (Indonesian Coffee and Cocoa Research Institute, 2016)
The low farm-gate price of agricultural commodities is commonly caused by low quality and complicated value chain. Quality improvement and direct selling through Mediated Partnership Model (Motramed) are conducted to increase farm-gate price and bargaining power of smallholder farmers. In Indonesia, Motramed has been applied in several coffee producing regions, such as Flores, Kintamani and East Java. This research aimed to understand the influence of quality improvement and direct selling activities through Motramed on market chain, farm-gate price and household coffee farmers’ income in Indonesia. This research was conducted in Kintamani in 2013. This research also used farm-gate data in several specialty coffee producing regions, including Flores (Bajawa and Ruteng), Kintamani and East Java that collected during 2010 and 2011. I incorporated both quantitative and qualitative research methods to explore and analyse the data. Household farmer survey, semi-structured interview with coffee stakeholders including farmers, collectors, exporters, government officials and NGOs; and field observation were used for collecting the data. The research shows that quality improvement activity in the farm level and direct selling through Motramed has